1988
DOI: 10.1007/bf00421057
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme alterations in experimental and clinical diabetes

Abstract: Previous studies from our laboratory have demonstrated the presence of complex alterations in the activities of antioxidant enzymes in various tissues of rats with streptozotocin (STZ)-induced diabetes. In the present investigation, it is shown that rats made diabetic with alloxan (ALX), an agent differing from STZ both chemically and in its mechanism of diabetogenesis, show virtually identical tissue antioxidant enzyme changes which, as is the case with STZ, are preventable by insulin treatment. The finding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
93
3
21

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(139 citation statements)
references
References 34 publications
18
93
3
21
Order By: Relevance
“…This is important because the myocardium is vulnerable to oxidative injury due to low levels of antioxidant enzymes found in these tissues. 2s, 26 Our intention is to substantiate this finding with expanded study ofpropofol's antioxidant potential during ACBP. This study was designed to find the appropriate dose of propofol to enhance red cell antioxidant status, not to find the appropriate dose for optimal hemodynamic stability.…”
Section: Discussionmentioning
confidence: 88%
“…This is important because the myocardium is vulnerable to oxidative injury due to low levels of antioxidant enzymes found in these tissues. 2s, 26 Our intention is to substantiate this finding with expanded study ofpropofol's antioxidant potential during ACBP. This study was designed to find the appropriate dose of propofol to enhance red cell antioxidant status, not to find the appropriate dose for optimal hemodynamic stability.…”
Section: Discussionmentioning
confidence: 88%
“…Diabetes mellitus should be associated with increased oxidative stress because blood concentrations of lipid peroxides increase in experimental and clinical diabetes (1,2). Oxidative stress means the production of highly reactive oxygen radicals that are toxic to the cells, par ticularly to the cell membrane in which these radicals interact with the lipid bilayer and produce lipid peroxides (3).…”
mentioning
confidence: 99%
“…For instance, a significant increase in GSH-Px (Godin et al, 1988;Kakkar et al,1995;Duncan et al,1996;Ray et al, 2007), CAT (Matkovics et al, 1982;Yadav et al,1997;Ray et al, 2007), and SOD activity (Garcia-Alfonso et al, 1995;Ray et al, 2007) and decrease in GSH-Px (Senator et al, 2004;Sindhu et al, 2005), CAT (Kakkar et al,1995, Sommerburg et al, 2002 and SOD activity (Kakkar et al, 1995;Senator et al, 2004) has been noted during oxidative stress injury depending on the experimental conditions. However, in the current study, paraquat significantly reduced the activity and expression of SOD, the activity of CAT with no significant change in CAT expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, under diabetic conditions in which oxidative stress plays an important role in the development of complications involving oxidant injury (Maiese et al, 2007;Kaneto et al, 2007), SOD activity has been shown to be reduced (Godin et al, 1988) or unaffected , CAT activity increased (Matkovics et al, 1982;Yadav et al,1997) or unaffected (Kakkar et al,1995) and GSH-Px activity increased (Godin et al, 1988;Kakkar et al, 1995;Duncan et al, 1996) or decreased (Tagami et al, 1992;Van den Branden et al, 2000). Antioxidant enzyme activities are also altered in chronic renal failure (CRF) in which oxidative stress also plays an important part (Modlinger et al, 2004), however, as with diabetic conditions, the true effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%